2022
DOI: 10.1063/5.0096771
|View full text |Cite
|
Sign up to set email alerts
|

Frequency chirp effects on stimulated Raman scattering in inhomogeneous plasmas

Abstract: Previous studies have shown that the use of laser bandwidth may mitigate the growth of stimulated Raman scattering (SRS) in laser plasma interaction experiments, in particular, when the spectrum of the driving (or pump) laser is composed of uniformly distributed frequency components with a well-chosen bandwidth [for example, Luo et al., Phys. Plasmas 29, 032102 (2022); Wen et al., ibid. 28, 042109 (2021); and Follett et al., ibid. 26, 062111 (2019)]. Here, we investigate the effects of frequency chirp in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Recently, it was observed that a negative frequency chirp rate can expand the phase-locking area and thus promote the development of the EPW and SRS. However, this phase-locking can be disrupted and the instability can be suppressed by a positive frequency chirp [37]. Similarly, using a rippled plasma density profile has also been shown to decrease the growth of the SRS instability [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was observed that a negative frequency chirp rate can expand the phase-locking area and thus promote the development of the EPW and SRS. However, this phase-locking can be disrupted and the instability can be suppressed by a positive frequency chirp [37]. Similarly, using a rippled plasma density profile has also been shown to decrease the growth of the SRS instability [38][39][40].…”
Section: Introductionmentioning
confidence: 99%